What are the first and second derivatives of f(x)=ln(1-x)^(3/2) ?

1 Answer
Dec 30, 2015

Assuming that what you meant was ln^(3/2)(1-x), we can apply chain rule twice here.

Explanation:

  • Chain rule: (dy)/(dx)=(dy)/(du)(du)/(dv)(dv)/(dx)

Where f(x)=u^(3/2), u=ln(v) and v=1-x.

(df(x))/(dx)=(3u)^(1/2)/2(1/v)(-1)

Substituting u:

(df(x))/(dx)=-(3(ln(v))^(1/2))/(2v)

Substituting v:

(df(x))/(dx)=color(green)((3sqrt(ln(1-x)))/(2(x-1)))

The second derivative falls into the same logic for chain rule in the numerator. However, we have a fraction, which will demand quotient rule.

  • Quotient rule: be y=f(x)/g(x), then y'=(f'g-fg')/g^2

(df(x)^2)/(d^2x)=(((3/2u^(-1/2))(1/v)(-1))(2(x-1))-3sqrt(ln(1-x))(2)}/(4(x-1)^2)

Substituting u:

(df(x)^2)/(d^2x)=(((3/(2sqrt(ln(v)))(1/v)(-1))(2(x-1))-6sqrt(ln(1-x))))/(4(x-1)^2)

Substituting v:

(df(x)^2)/(d^2x)=(((3/(2sqrt(ln(1-x)))(1/(1-x))(-1))(2(x-1))-6sqrt(ln(1-x))))/(4(x-1)^2)

(df(x)^2)/(d^2x)=((cancel(-)6cancel((x-1)))/(2cancel((1-x))sqrt(ln(x-1)))-6sqrt(ln(1-x)))/(4(x-1)^2)

(df(x)^2)/(d^2x)=((3-6ln(1-x))/(sqrt(ln(1-x))))/(4(x-1)^2)=color(green)((3-6ln(1-x))/(4(x-1)^2sqrt(ln(1-x))))